Analysis of drain current transient stability of AlGaN/GaN HEMT stressed under HTOL & HTRB, by random telegraph noise and low frequency noise characterizations. (November 2020) - Tartarin, J.G.; Lazar, O.; Rumeau, A.; Franc, B.; Bary, L.; Lambert, B.
Abstract: The charges in wide bandgap gallium nitride (GaN) High Electron Mobility Transistors (HEMT) can be identified by means of various methods such as electrical transient and pulsed measurements, or noise spectroscopy methods, usually performed at different temperatures to extract activation energies. These traps can be passivated or activated according to electrical or thermal conditions over the lifetime. Therefore, the distinction between harmful traps (with consequences on performances) and harmless traps (without impact on electrical behavior) must be performed. In this paper, devices stressed by HTOL (High Temperature Operating Life) are characterized by time domain electrical techniques (transient and pulsed), and with low frequency noise (LFN) experimental tools. By performing characterizations on the gate and on the drain, it is also possible to identify the drain current sensitivity to charges located in specific regions of the transistor (command or channel zones). The proposed case study discriminates the traps in the GaN buffer and at the vicinity of the AlGaN/GaN interface. The HTOL stress impacts the traps at the interface border zone in the AlGaN layer. This causes a drift in the threshold voltage Vth, also with a hysteresis depending on direction of increasing or decreasing sweep of the gate voltage during the characterization. Also the Schottky diode leakage current profile at the transition voltage between forward and reverse biasing mode has been analysed versus temperature. The thermal sensitivity of the drift of the threshold voltage and of the transition voltage is attributed to the kinetics of ionization and neutralization of the donor traps with the applied gate voltage. This drift of Vth, and the action of many other traps or charges, cause the drain current to vary over time. These results are finally compared to those obtained by HTRB stress (High Temperature Reverse Bias), presenting similar degradation signatures over a longer stress period. Highlights: Charges in GaN HEMT devices need to be located to be mastered. Cross analysis between transient and pulsed electrical measurements with low frequency noise on gate and drain current Location of active traps, evaluation of their effect on the threshold voltage Threshold voltage drift with temperature and with HTOL stress HTOL stress activates donor traps below the gate.